Trade reforms, deforestation and industrial pollution in developing countries: One size does not fit all - Ian Coxhead; Sisira Jayasuriya (Osaka University, Institute of Social and Economic Research (ISER), 2005)
Many developing countries possess comparative advantage both in natural resources and in labor-intensive industries, and experience both industrial pollution and natural resource degradation. We present a model that incorporates these stylized facts together with key spatial features and property rights failures typical of developing economies. We explore consequences of anticipated domestic and global trade policy and world price changes. Similar exogenous or policy shocks are seen to have contrasting effects, depending on initial economic structure, trade orientation and policy regime. Further, when there is more than one sectoral source of environmental damage, a policy or price change may have unexpected environmental and welfare results. Nevertheless, in many empirically important cases, reducing protection for capital intensive manufactures is likely to improve both income and environmental quality, a point that we illustrate by reference to some Asian case studies. These results stand in contrast to those obtained in much of the current analytical literature.
Keywords: F18; O24; Q28; 330; trade; environment; pollution; deforestation; developing countries; Handelsliberalisierung; Entwaldung; Umweltbelastung; Entwicklungsländer